1996
DOI: 10.1159/000244375
|View full text |Cite
|
Sign up to set email alerts
|

Neither Motor Responses nor Gastric Emptying Vary in Response to Formula Temperature in Preterm Infants

Abstract: The purpose of this study was to assess gastrointestinal responses to formula temperature in preterm infants. Healthy preterm infants were fed 4,250 KJ/1 formula at 6, 24, and 37° C. There was no significant difference in the magnitude of antral or duodenal motor responses among the three temperatures. All infants emptied approximately one third of the bolus feeding by 20 min, but there was no difference among the temperatures. Approximately 10–20% of a bolus feeding remained in the stomach 2 h postprandially,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Furthermore, the functional significance of thermoreceptors has not been confirmed. Studies have shown conflicting results [1]. However, the absence of reaction to the stimulus applied by drinking cold water is more probably a result of central inhibition since there are cold-specific receptors in the mouth and larynx [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the functional significance of thermoreceptors has not been confirmed. Studies have shown conflicting results [1]. However, the absence of reaction to the stimulus applied by drinking cold water is more probably a result of central inhibition since there are cold-specific receptors in the mouth and larynx [1,10].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric functioning was examined in 5 studies. 15,[17][18][19][20] No differences in infants' antral or duodenal motor activity was observed among cold, room, and/or body temperature feeding groups. 18 Three research teams observed that the temperature of feedings made no difference in the percentage of feeds retained in the stomach.…”
Section: Physiological Effects Of Milk Temperatures On Infantsmentioning
confidence: 91%
“…15,[17][18][19][20] No differences in infants' antral or duodenal motor activity was observed among cold, room, and/or body temperature feeding groups. 18 Three research teams observed that the temperature of feedings made no difference in the percentage of feeds retained in the stomach. [18][19][20] However, Gonzales et al 15 noted significantly lower gastric residuals in the body temperature group (6%) compared with the cool (18%) and room temperature (22%) groups.…”
Section: Physiological Effects Of Milk Temperatures On Infantsmentioning
confidence: 91%
See 1 more Smart Citation
“…There were ten infants in each group, a very small number from which to draw conclusion and upon which to base changes in practice. One additional study had a similar design; feeding the same three temperatures of 10 C, 24 C and 37 C. 15 This study included 20 infants in a crossover design with gestational ages 32 to 36 weeks. In this study, residuals were measured two hours after the feeding but no significant difference was found between the groups.…”
Section: Accepted Manuscriptmentioning
confidence: 99%